KEJADIAN STUNTING PADA BALITA; STUDI CASE-CONTROL DI PUSKESMAS BASTEM LUWU - Umrah, Andi Sitti; Dahlan, Andi Kasrida; Mansyur, Nurliana (Universitas Muhammadiyah Mataram, 2021)
Abstract: Stunting is a condition of stunted growth in children under five due to chronic malnutrition for a long time so that the child is shorter than their supposed age. This study aims to analyze the risk factors for food availability, maternal nutritional status during pregnancy, and nutritional intake on the incidence of stunting in toddlers aged 24-59 months in the Bastem Community Health Center working area. The research method uses a case-control study. Samples were toddlers aged 24-59 months in Puskesmas Bastem. The sampling technique was simple random sampling. The sample was divided into 2 (two) parts: the case and control groups, with as many as 19 people in each group. The analysis technique used the chi-square test and logistic regression. The results of statistical tests showed that food availability (p = 0,022; OR = 10,40), maternal nutritional status (p = 0,007; OR = 2,41), nutritional intake (p = 0,003; OR = 6,69) on the incidence of stunting. Food availability is one of the most risk factors for stunting in under-five children in the Bastem Health Center area.Abstrak: Stunting merupakan keadaan terhambatnya pertumbuhan pada balita yang disebabkan kekurangan gizi kronis dalam waktu lama, sehingga anak lebih pendek dari usia seharusnya. Penelitian ini bertujuan untuk menganalisis faktor risiko ketersedian pangan, status gizi ibu selama hamil, dan asupan gizi terhadap kejadian stunting pada balita usia 24-59 bulan di wilayah kerja Puskesmas Bastem. Metode penelitian menggunakan case control study. Sampel adalah balita usia 24-59 bulan diwilayah Puskesmas Bastem, tehnik penarikan sampel secara simple random sampling. Sampel dibagi menjadi 2 (dua) bagian yaitu kelompok kasus dan kelompok kontrol, sebanyak 19 orang pada masing-masing kelompok. Tekhnik analisis menggunakan uji chi-square dan regresi logistik. Hasil uji statistik diperoleh ketersedian pangan (p = 0, 022 ; OR = 10,40 ), status gizi ibu (p = 0,007 ; OR = 2,41), asupan gizi (p = 0,003 ; OR = 6,69) terhadap kejadian stunting. Ketersedian pangan merupakan salah satu faktor risiko yang besar terjadinya stunting pada balita di wilayah Puskesmas Bastem.